(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This scientific article thoroughly analyzes the role and importance of artificial intelligence (AI) technologies in teaching English to primary school students. The study highlights the role of tools based on artificial intelligence in individualizing the educational process, developing students’ speech activity, and increasing their motivation. The effectiveness of interactive platforms, speech recognition systems, and chat bots used in primary education is also scientifically substantiated. The research results show that artificial intelligence tools are an important factor in optimizing the educational process and improving the quality of education.